ESG ACTIVITIES AND BANK EFFICIENCY: ARE ISLAMIC BANKS BETTER? - Ahmed W. Alam; Hasanul Banna; M. Kabir Hassan (Journal of Islamic Monetary Economics and Finance, 2022)
In this paper, we investigate the differential impact of ESG activities on banks’ technical efficiency for conventional and Islamic banks. We employ a Data Envelopment Analysis (DEA) technique to determine the efficiency scores of the banks. Based on a sample of 14 conventional and 11 Islamic banks from 4 countries over the period 2011 - 2019, we find that average DEA-generated efficiency of conventional (Islamic) banks is about 38.8% (42.45%). Baseline Tobit regressions suggest that ESG has an overall positive impact on banks’ efficiency. Further, we analyze the relationship for conventional and Islamic banks separately. We find that the positive effect sustains for conventional banks but turns out to be insignificant for Islamic banks. Our individual ESG dimension-wise analyses suggest that environmental activities positively influence the efficiency of both conventional and Islamic banks, whereas social activities strengthen the efficiency of conventional banks only. We do not find any significant result in favor of governance-related initiatives. Our baseline results survive the robustness test based on Simar and Wilson (2007) two-stage efficiency analysis. Based on our findings, we argue that Islamic banks lack sufficient investment on ESG friendly initiatives. We recommend that Islamic banks increase their awareness of the benefits of ESG practices and pay attention to improve their overall and dimension-wise ESG scores with a goal to improve their banking efficiency.